ANALISIS KEMAMPUAN LITERASI DAN NUMERASI SISWA KELAS V SEKOLAH DASAR - Tiara Nur Cahyani; Een Unaenah; Erdhita Oktrifianty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Literacy and numeracy skills are the ability to use various kinds of numbers and symbols in basic mathematics, the ability to analyze the information displayed, and the ability to interpret answer results. This research method is descriptive research with a qualitative approach. This research aims to determine students' literacy and numeracy abilities in solving circle diagram problems. Data collection techniques use test and interview methods. The analysis techniques used are data reduction, data presentation, and drawing conclusions. The subjects in this research were class V-A students at SD Negeri Cibodas 5, Tangerang City, totaling 16 students, consisting of 2 students with high initial abilities, 5 students with medium initial abilities, and 9 students with low initial abilities. Based on the results of data analysis, it can be concluded that the students with the highest literacy and numeracy ability test scores can meet 3 indicators, then students with medium category literacy and numeracy ability test scores can meet 2 indicators, while students with the lowest numeracy literacy test scores only meet 1 indicator